Лирика: поэзия / С. Черный - Черный Саша (Харвест, 2002)
Экземпляры: аб. (2003) / Инвентарный номер: 46257 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Ч-49 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5